Exploring QRIS Continuance Use Intention Among Generation Z: Integrating TAM and ECM with Trust and Perceived Risk as Moderators - Friska Nur Areta Puri; Datien Eriska Utami (Journal of Enterprise and Development (JED), 2026)
Purpose: This study aims to investigate the impact of perceived value and service quality on the continuance use intention of QRIS among Generation Z, with user satisfaction serving as a mediating variable, and trust and perceived risk as moderating variables.Method: A quantitative research approach was employed, utilizing a survey conducted with 240 Generation Z respondents in Solo Raya who have used QRIS in their daily transactions. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software.Result: The findings indicate that both perceived value and service quality positively influence user satisfaction. Additionally, perceived value and user satisfaction significantly affect continuance use intention. Although service quality does not have a direct effect, it indirectly influences continuance use intention through user satisfaction. Trust and perceived risk, however, do not moderate the relationship between user satisfaction and continuance use intention.Practical Implications for Economic Growth and Development: This study supports Indonesia's digital economy agenda by identifying strategies to sustain QRIS adoption among youth. By strengthening perceived value and service quality, QRIS can enhance financial inclusion, improve transaction efficiency, and foster the digital integration of MSMEs.Originality/Value: This study offers a unique contribution by integrating the Technology Acceptance Model (TAM) and the Expectation Confirmation Model (ECM) within the QRIS context. It also examines trust and perceived risk as moderators between user satisfaction and continuance use intention.